Commodity price shocks, fiscal performance and growth. A proposal of structural VAR for the Argentine economy - Lanteri, Luis N. (Estudios Económicos de El Colegio de México, 2008)
The international prices of commodities have increased markedly in recent years, driven by growth in China, India and other developing countries, which has had a positive impact on the economies of exporting these products. This paper analyzes the dynamics of changes in the prices of commodities on output growth and fiscal variables, in the case of Argentina. To this end, we use a structural VAR approach, with short-term restrictions, which allows nominal shocks in the international prices of commodities affect tax revenues, government consumer expenditures and output growth.